Prediksi Risiko Sistematik Saham-Saham LQ45 Bursa Efek Indonesia - A An Arief Jusuf (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2014)
Beta has been argued, both conceptually as well as empirically. In 1960's, many practitioners used superior advantages in calculation attempted at CAPM theory for investing in asset which has high Beta. Many empirical researches on the later years refused the existence of security market line from CAPM. Afterwards, many practitioners and academicians stated the death of CAPM. Linear regression method could be used to make decision if it had already matched the criteria for Best Linear Unbiased Estimator. Prediction model is a statistic testing which aimsat knowing whether there is a relationship or effect between researched variables. Nonparametric method is an alternative action which is taken when the research model does not match normality assumption. This research, as shown by the use of weekly data, could be free from technical trading problems in predicted systematic risk. While ASII, HRUM, and TLKM stock returns are affected more by other factors. This condition has caused systematic risk not to affect significantly on those stocks. Another result has shown that banking stocks, which became part of LQ45, have higher systematic risk respectively.